2022
DOI: 10.31219/osf.io/fn8y5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infants’ looking preferences for social versus non-social objects reflect genetic variation

Abstract: To what extent do individual differences in infants’ early preference for faces versus non-facial objects reflect genetic and environmental factors? In a sample of 536 5-month-old same-sex twins, we assessed attention to faces using eye-tracking in two ways: initial orienting to faces at the start of the trial (thought to reflect subcortical processing) and sustained face preference throughout the trial (thought to reflect emerging attention control). We show that both face orienting and preference were herita… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 41 publications
(65 reference statements)
1
13
0
Order By: Relevance
“…In particular, preferential attending to eye and mouth regions of the face was the most heritable of the social attention characteristics measured in their study (Constantino et al., 2017), a finding consistent with what was later reported with regard to attention to faces relative to nonsocial objects by Portugal et al. (2022). Although the exact genes involved were not investigated in these studies, previous research demonstrated that the oxytocin receptor gene (OXTR) is involved in modulating infant neural response to emotional faces (Krol, Puglia, et al., 2019).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In particular, preferential attending to eye and mouth regions of the face was the most heritable of the social attention characteristics measured in their study (Constantino et al., 2017), a finding consistent with what was later reported with regard to attention to faces relative to nonsocial objects by Portugal et al. (2022). Although the exact genes involved were not investigated in these studies, previous research demonstrated that the oxytocin receptor gene (OXTR) is involved in modulating infant neural response to emotional faces (Krol, Puglia, et al., 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, it is also possible that social attention in infancy is not subject to much environmental influence (Constantino et al, 2017;Portugal et al, 2022). Constantino et al (2017) found that the way infants view social scenes is strongly influenced by genetic factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations